PENGEMBANGAN e-LKPD BERBASIS STEAM BERBANTU CANVA POKOK BAHASAN MATERI DAN PERUBAHANNYA PADA PEMBELAJARAN BERDIFERENSIASI DI SEKOLAH DASAR - Estuhono, Estuhono; Ratnawati, Ratnawati; Arista, Ridho Bela (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2024)
The problem in this study is due to the limited use of electronics, especially related to STEAM. The purpose of this research is to produce STEAM-based e-LKPD assisted by CANVA on the subject matter of matter and its changes to support differentiated learning in elementary schools. The type of research conducted is Research and Development (R&D). The development model uses ADDIE. The research sample was 27 students. Based on the results of data on the validation test, 84.09% (language), 89.28% (practicality) with a very valid category. (2) Validation test, 94.44% (teaching module), 91.66% (material) with a very valid category. Validation test, 94.64% (graphics), 97.5% (presentation construct) with a very valid category. Validation test, 76.92 (test) with valid category. The implications for the development of STEAM-based e-LKPD assisted by CANVA can be used to improve student learning outcomes.